2019
DOI: 10.1007/s10826-019-01583-6
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Mindfulness-Based Intervention with Sheltered Youth Experiencing Homelessness

Abstract: Objectives Evidence of the acceptability and potential efficacy of mindfulness strategies with at-risk youth is mounting. Yet only a few studies have assessed these strategies among youth experiencing homelessness (YEH). Methods We conducted a mixed methods feasibility study of an adapted mindfulness-based intervention (MBI) with sheltered YEH. The MBI consisted of five 1.5-h sessions delivered at a youth homeless shelter over 2.5 weeks. A one-group pre/post-test design was utilized to collect quantitative ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 90 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…Mindfulness is described as an intentional and non‐judgmental awareness of the present moment that can foster self‐regulation, self‐observation, self‐control, greater awareness of cognitions and emotions that can lead to cognitive and emotional reappraisal, less reactivity, and improved interpersonal relationships (Alhusen, Norris‐Shortle, Cosgrove, & Marks, 2017; Goyal et al, 2014; Shapiro, Carlson, Astin, & Freedman, 2006; Siegel & Williams, 2003). Santa Maria et al (2019) adapted MBI with 39 sheltered youth experiencing homelessness, between 18 and 21 years old. The authors utilized a mixed‐method study to assess the feasibility and acceptability of an existing mindfulness curriculum with youth residing in a homeless shelter.…”
Section: Current Interventions For People Without Homes and The Impri...mentioning
confidence: 99%
“…Mindfulness is described as an intentional and non‐judgmental awareness of the present moment that can foster self‐regulation, self‐observation, self‐control, greater awareness of cognitions and emotions that can lead to cognitive and emotional reappraisal, less reactivity, and improved interpersonal relationships (Alhusen, Norris‐Shortle, Cosgrove, & Marks, 2017; Goyal et al, 2014; Shapiro, Carlson, Astin, & Freedman, 2006; Siegel & Williams, 2003). Santa Maria et al (2019) adapted MBI with 39 sheltered youth experiencing homelessness, between 18 and 21 years old. The authors utilized a mixed‐method study to assess the feasibility and acceptability of an existing mindfulness curriculum with youth residing in a homeless shelter.…”
Section: Current Interventions For People Without Homes and The Impri...mentioning
confidence: 99%
“…In the pilot study, we tested the feasibility and acceptability of using a slightly modified version of the . b curriculum among 39 sheltered YEH aged 18–21 years [ 64 ]. Though the program is usually delivered in a school setting over multiple weeks, in the shelter environment, in the pilot study, we had to make modifications to approximate the average time YEH spend in a shelter.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we delivered the lessons in five 90-minute long sessions over 2.5 weeks. Though the results of the pilot intervention showed feasibility, findings also suggested that more substantial modifications were needed to improve its relevance and accessibility of the intervention for YEH and to ensure a trauma-informed approach [ 64 ]. In this paper, we present the adaptation process of the .…”
Section: Methodsmentioning
confidence: 99%
“…We demonstrated that YB stimulates 1) reductions in levels of salivary pro-inflammatory biomarkers [37], 2) induction of the neuromodulator Nerve Growth Factor (NGF), which is important for maintenance and survival of the peripheral and central nervous system [38], and 3) alterations in the levels of proteins associated with tumor suppression and immune regulation [39]. Although mobile Apps provide a convenient way to provide mindfulness exercises and could reduce barriers of delivery intervention [40][41][42], adherence to such apps is at very low rates [43,44].…”
Section: These Early Studies Though Correlative Provide the First Evi...mentioning
confidence: 99%